Cultural Semantics and Linguistic Worldviews: A Comparative Study of English Individualism and Russian Collectivism (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Language is a complex, unique sign system, a universal means of communication. Language reflects the features of history, geography, everyday life, culture and literature of the people who speak it. Thus, a cumulative function—known in linguistics as the “cultural component of the meaning of a word”—is distinguished alongside the communicative function. This function consists of storing and transmitting the extra linguistic experience of a particular linguistic community, which determines the content of extralinguistic information in a linguistic sign. In this way, language serves as a sort of intergenerational bridge, preserving and passing along people's extra linguistic experiences.